Haplotype Analysis of Identical Factor IX Mutants Using PCR - Green, Peter M; Montandon, A Jane; Ljung, Rolf; Nilsson, lnga Marie; Giannelli, Francesco (Thrombosis and Haemostasis, 1992)
We have detected the mutations in the factor IX genes from all of the haemophilia B patients registered at Malmo haemophilia centre (45) and are currently examining the entire UK haemophilia B population. From these studies we have found 13 base substitutions which have recurred in 1-6 other, presumably unrelated, patients. In order to determine the minimum number of independent repeats of each mutation we have used PCR to examine the five factor IX polymorphisms forming the most informative combinations and we have characterised the haplotype of each patient. Patients with different haplotypes are assumed to be unrelated and thus to carry independent mutations. All but one of the 13 mutations occur in at least 2 haplotypes thus pinpointing 12 mutational hotspots and mutations that can be clearly considered detrimental. Two of the 13 substitutions occur at non-CpG sites.